Assessing Technical, Functional And Image Aspects Of Service Quality And Their Impact On Citizen Satisfaction - As-Sajjad, Muhammad Dzaky; Agustina, Iin; Wiradiputra, Indra Aldila (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2023)
This study aims to examine how the influence of technical aspects, functional aspects, and image on the service quality in Cibeunying Kidul District, Bandung, and how the quality of these services has an impact on citizen satisfaction as service users. By using a quantitative approach, the research sample was determined by convenience sampling technique. The selected research respondents were people who had used services at the Cibeunying Kidul Bandung District Office and were willing to voluntarily participate in the research. During the two-month study period, there were 89 respondents who were willing to participate and filled out a questionnaire that was sent online. The data that has been collected is analyzed using path analysis. The results of the study show that only technical and functional aspects can affect service quality in Cibeunying Kidul District, Bandung. Meanwhile, service quality has a very large influence on citizen satisfaction in Cibeunying Kidul District, Bandung. These results provide important implications for public organizations in an effort to increase citizen satisfaction and as an effort to encourage an increase in the quality of public services provided, especially by looking at the most important aspects that reflect of these services quality.